PEX11β and FIS1 cooperate in peroxisome division independently of mitochondrial fission factor - Schrader, Tina A.; Carmichael, Ruth E.; Islinger, Markus; Costello, Joseph L.; Hacker, Christian; Bonekamp, Nina A.; Weishaupt, Jochen H.; Andersen, Peter M.; Schrader, Michael (Journal of cell science, 2022)
Peroxisome membrane dynamics and division are essential to adapt the peroxisomal compartment to cellular needs. The peroxisomal membrane protein PEX11β (also known as PEX11B) and the tail-anchored adaptor proteins FIS1 (mitochondrial fission protein 1) and MFF (mitochondrial fission factor), which recruit the fission GTPase DRP1 (dynamin-related protein 1, also known as DNML1) to both peroxisomes and mitochondria, are key factors of peroxisomal division. The current model suggests that MFF is essential for peroxisome division, whereas the role of FIS1 is unclear. Here, we reveal that PEX11β can promote peroxisome division in the absence of MFF in a DRP1- and FIS1-dependent manner. We also demonstrate that MFF permits peroxisome division independently of PEX11β and restores peroxisome morphology in PEX11β-deficient patient cells. Moreover, targeting of PEX11β to mitochondria induces mitochondrial division, indicating the potential for PEX11β to modulate mitochondrial dynamics. Our findings suggest the existence of an alternative, MFF-independent pathway in peroxisome division and report a function for FIS1 in the division of peroxisomes.This article has an associated First Person interview with the first authors of the paper.